Case study on a potential application of failure mode and effects analysis in assessing compliance risks - Ferenc Bognár; Petra Benedek (Risks, 2021)
Assessing and reducing compliance risks can now be considered one of the core criteria for business success. While failure mode and effect analysis (FMEA) is widely used in engineering, its application in the financial sector is quite novel, primarily related to compliance risk assessment. This paper presents the results of exploratory research based on the potential application of FMEA in a focus group of compliance experts at one of the largest Central and Eastern European commercial banks. This study aims to establish a process for assessing compliance risks that builds on the strengths of both the qualitative and quantitative assessment methods. Applying FMEA based on a nominal group technique and further statistical analysis provides an opportunity to compare expert assessments and the consensus level of the participants. As a result, the similarity or difference of the assessment patterns can be quantified, providing objective feedback on the evaluation. Finally, this paper proposes lifting the detectability of failures as an evaluation dimension to the same level of importance as the probability and impact of non-compliance and using agreement testing statistical methods.
Keywords: 330; compliance risks; FMEA; risk assessment